Training of Tegal Bungur Village Apparatus, South Lampung, in Preparing Local Culture-Based Tourism Villages - Bursan, Rinaldi; Ramelan, Mudji Rachmat (Indonesian Journal of Community Services Cel, 2024)
This community service was carried out in Tegal Bungur Village, South Lampung Regency, with the main objective of increasing the village officers' understanding of the concept of local culture-based tourism and equipping them with tourism management skills. This activity applies the 7D approach method (Discover, Define, Design, Develop, Deliver, Deploy, Document), which took place in September 2024. This training was attended by 30 participants covering various elements of the Tegal Bungur Village community, consisting of five village officials, three administrators of Village-Owned Enterprises (BUMDes), 15 young men and women members of Karang Taruna, five housewives, and two religious figures. The community empowerment process includes three main stages: initial survey, program implementation, and evaluation of results. The results of this activity showed a significant increase in the knowledge (25%), skills (25%), and attitudes (35%) of training participants, consisting of village officials who aim to develop tourist villages. This capacity increase is reflected in the ability of participants to prepare strategic work plans, including the formation of Tourism Awareness Groups (Pokdarwis) as the main driving force for tourism activities in the village. In addition, several innovations have begun to be designed, such as holding an annual cultural festival and developing a local family-based homestay program. To ensure the sustainability of this program, collaborative support is needed from all elements of society, including the younger generation and local business actors. This support is expected to create a sustainable tourist village and provide a positive economic impact for all villagers.